THE EFFECT OF PROJECT BASED LEARNING LEARNING MODELS ON THE LEARNING OUTCOMES OF PPKN VII GRADE STUDENTS SMP PGRI MUMBULSARI - Syafi’i Imam (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2022)
Project-based learning focuses on hands-on learning, real-life assignments, or at least integration of learning materials with the real life of everyday life. In fact, this learning model is a contextual education family and a learning model or approach, the development of project-based learningRecently, online or online learning has been carried out a lot in order to stop the spread of the corona virus. Online learning is intended to avoid direct contact between teachers and students and between students themselves with the intention of preventing transmission The respondents of this study were 65 students of class VII SMP PGRI Mumbulsari, and the research area was determined using a purposive sampling method. This research is a quantitative research with a causal design. Data collection tools use questionnaires, tests, and documentation as well as interview aids. The validity and reliability of the instrument and the degree of validity and reliability of the test. Instrumental analysis tests used: 1) Descriptive Test, 2) Normality Test, 3) Homogeneity Test. Test the hypothesis with: 1) t-test and 2) F-test. The research results show the following: 1) Signature value. From the project-based learning variable of 0.000, the result is a signal. > 0.05 means that there is a project-based learning model for learning outcomes, 2) signal value. From the online variable of 0.000, the conclusion is sig. > 0.05 means that there is an online learning model for learning outcomes, 3) The results of the Fcount 31,654 regression analysis obtained a signature. 0.000, because > 0.05, there are joint project-based learning and online learning models around student learning outcomes. The assumptions made in this study are that project-based learning and online learning can be applied properly in the teaching and learning process because they can affect learning outcomes